VIGILÂNCIA DA TRANSMISSÃO VERTICAL DE INFECÇÕES SEXUALMENTE TRANSMISSÍVEIS EM UM SERVIÇO DE ATENÇÃO TERCIÁRIA - Giacomini, Margarete Reginatto (2017)
The objective of the present study was to delineate the epidemiological profile of pregnant women diagnosed with HIV/aids, syphilis and hepatitis B and C, notified in 2015, in a tertiary care regional referral service. As specific objectives: to present the epidemiological profile of the pregnant women notified in 2015 to the group responsible for the Maternal and Child Care Line of the hospital where the research was carried out, and to prepare a newsletter aiming at helping the visibility of the data to list the priorities of the team's actions. This is a cross-sectional retrospective study performed at a reference hospital in the central region of Rio Grande do Sul. Data collection took place in November and December 2016 and January 2017, through consultation in the system and notification forms of the Nucleus of Hospital Epidemiological Surveillance. From the survey, 179 cases of STI were identified in pregnant women in the year 2015. The age of women ranged from 15 to 41 years. The provenance of the pregnant women showed that many are coming from small municipalities of the central region of Rio Grande do Sul, considering that this hospital is a reference for this region. The product resulting from this work consisted of two articles of a newsletter, widely distributed and disseminated in the service in which the research was developed. As benefits, after the collection and analysis of the data, the results obtained were presented to the service, which allowed the knowledge of the situational diagnosis that could guide the planning of surveillance actions, prevention and control of the vertical transmission of STIs in municipalities of the 4th CRS, since HUSM is a reference in the hospital service for the region.